PENGARUH PROMOSI TERHADAP KEBERHASILAN USAHA PELAKU UMKM - Purnamasari, Dewi Laily; Hajijah, Sitta Nur; Ridho Rusydi, Ibrahim Rasyid; Amroni, Amroni (Jurnal EBI, 2024)
The development of micro, small and medium enterprises (MSMEs) has recently attracted theattention of the government, the local government has a very strategic role in growing thedevelopment of regional MSMEs, especially the Cirebon City Government. This study aims todetermine the influence of food product marketing on the business success of MSME actors.This research sample was obtained using purposive sampling techniques on food MSME actorslocated in the SME Mall in Cirebon city with a total of 55 people. Data collection usingGoogle Form questionnaire. This study used quantitative analysis with validity test, reliabilitytest, simple linear regression analysis test, partial test (T Test), coefficient of determination.The results showed that product marketing had a positive and significant effect on businesssuccess. The percentage of influence of food product marketing on the success of MSMEbusinesses in the SME Mall in Cirebon city can be interpreted that 30.2% and 69.8% areinfluenced by other variables that are not in the study.Keywords: product marketing, success, msme